The financing dynamics of newly founded firms - Julia Hirsch; Uwe Walz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
Little evidence exists on the financing decisions of newly founded firms or on the financing dynamics of these firms over their life cycle. We aim to help filling this gap by investigating the financing dynamics of 2,456 French manufacturing firms founded between 2004 and 2006 through their legally required and reported financial statements. Because we observe significant heterogeneity in the financing decision in the firms' founding year, we focus on analyzing whether these differences widen, persist, or converge by using different convergence concepts. We identify a persistence-cum-convergence pattern. We find the existence of ß-convergence (implying that e.g. firms with lower initial levels of debt accumulate more debt over time) but not of ß-convergence (i.e. we observe an increase in the cross-sectional dispersion of the financing structure). We also show that the dynamics of financing matter for the growth path of the firms.
urn:nbn:de:hebis:30:3-418726
Keywords: D92; G32; 330; financing decisions; life-cycle; firm growth; newly founded firms